ANALYSIS OF STRATEGY TO FULFILL THE NEED OF THE POPULATION OF JEMBER REGENCY FOR UNIVERSAL HEALTH COVERAGE IN REDUCING STUNTING, MATERNAL DAN INFANT MORTALITY RATES - Puspitasari, Febriana Maya (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This policy paper aims to analyze strategies for fulfillment the needs of the population of Jember Regency for Universal Health Coverage in reducing stunting, maternal and infant mortality. This is motivated by the results of the 2022 Indonesian Nutrition Status Survey which stated that Jember Regency was ranked highest in the prevalence of stunting under five in East Java Province and the East Java Provincial Health Service stated that Jember Regency's maternal and infant mortality rate was the highest in East Java Province. Meanwhile, the sustainable development goals (SDGs) in 2030 target reducing the maternal mortality rate to less than 70 per 100,000 live births, reducing the infant mortality rate (IMR) to 12 per 1,000 live births, reducing stunting by 14% by 2024. On the other hand , the population of Jember Regency who are JKN-KIS participants has only reached 66% of the total population, while Law Number 40 of 2004 concerning the National Social Security System (SJSN) and Presidential Instruction (Inpres) Number 1 of 2022 concerning Optimizing the Implementation of the Health Insurance Program National mandates that the entire population be protected by Universal Health Coverage of at least 98% by 2024. The analysis technique used in this policy paper is SWOT analysis. The strength of the internal factors is that the Jember Regency Government pays special attention to handling high stunting, maternal and infant mortality rates, including free services, continuous monitoring and evaluation, providing a budget, and making reducing stunting and maternal and infant mortality a priority for development in the health sector. and also the existence of Presidential Instruction Number 1 of 2022. The weaknesses are internal factors, namely the Universal Health Coverage budget allocation for the population of Jember Regency which is not enough, the Universal Health Coverage budget is also not yet a priority in the APBD budget allocation, the J-Pasti Kuereen program which can trigger participants Independent JKN-KIS does not pay its contributions, and there is a lack of interest among residents in becoming independent JKN-KIS participants. Meanwhile, the threat from external factors is that the JKN-KIS membership achievement of the Jember Regency population in June 2023 is still 66% of the target in 2024 of 98%, the public's demand for the quality of health services is increasing, the Maternal and Infant Mortality and Stunting rates in Jember Regency are the highest in all time. East Java Province. And the opportunity for external factors is the high attention of the Jember Regency Government to handling high levels of stunting, maternal and infant mortality, providing budget allocations in order to handle reducing stunting, maternal and infant mortality as well as the government's encouragement to realize Universal Health Coverage in Jember Regency. So that the proposed alternative strategy can be formulated, namely making Universal Health Coverage a priority in Jember Regency APBD budgeting in order to reduce stunting, maternal and infant mortality rates so that health services can be implemented preventively, promotively, curatively and rehabilitatively in order to create a health program that is covered by the JKN budget. -KIS so that it can be carried out in a comprehensive and integrated manner. There is APBD support in the budget allocation to support Universal Health Coverage for the residents of Jember Regency and a shift in the free health services budget to the Universal Health Coverage budget.